Tobacco Use Among Adolescent: A Burning Issue in Bhopal City - Bathma, Vishal; Likhar, Swarn; Agarwal, Sanjay; Mishra, Mahesh; Shukla, Uma (National Journal of Community Medicine, 2015)
Introduction: The young people of today are tomorrow's adults. Tobacco use is the chief preventable cause of illness & death all over the world. Objective of the study to estimate the prevalence and type of tobacco use among adolescent students in grade 8th, 9th and 10th in Bhopal city. Methods: School-based cross-sectional descriptive study was carried out among 2285 Adolescent students in Bhopal city. Data was collected by an anonymous self administered modified Global Youth Tobacco Survey Questionnaire and Data were analyzed by frequency distribution tables, chi square test and univariate logistic regression as required. Result: Out of 2285 adolescent student’s 415 (18.2%) ever used the tobacco product in one or other form. The use of tobacco was significantly higher amongst boys 335 (80.7%) as compared to girls 80 (19.3%). Use of tobacco was more in governmental schools 257 (61.9%) as compared to non-governmental schools 158 (38.1%). The use of tobacco was most common in age group 12-15 years 355 (85.5%). It is observed in our study that amongst all tobacco users, maximum 199 (47.95%) were experimental users. maximum no. of students 271 (65.3%) were using pan masala and gutkha. Conclusion: Non-smoking forms of tobacco like pan masala and gutkha, were more commonly used by students. The majorities of them are experimental users, but if not addressed right now will be potential regular users in the future.